2019
DOI: 10.1038/s41467-019-11860-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial dynamin-like protein IniA mediates membrane fission

Abstract: Mycobacterium tuberculosis infection remains a major threat to human health worldwide. Drug treatments against tuberculosis (TB) induce expression of several mycobacterial proteins, including IniA, but its structure and function remain poorly understood. Here, we report the structures of Mycobacterium smegmatis IniA in both the nucleotide-free and GTP-bound states. The structures reveal that IniA folds as a bacterial dynamin-like protein (BDLP) with a canonical GTPase domain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…Our complementation analyses indicated IniA and IniC have non-redundant functions in EV biogenesis supporting the idea that these DLPs work together. This is in agreement with Wang et al who observed low GTPase activity in monomeric Msm -IniA and suggested that interactions with IniC may be required for high rates of GTP hydrolysis (22). This form of cooperation was described for mitochondrial OPA1 proteins.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our complementation analyses indicated IniA and IniC have non-redundant functions in EV biogenesis supporting the idea that these DLPs work together. This is in agreement with Wang et al who observed low GTPase activity in monomeric Msm -IniA and suggested that interactions with IniC may be required for high rates of GTP hydrolysis (22). This form of cooperation was described for mitochondrial OPA1 proteins.…”
Section: Discussionsupporting
confidence: 92%
“…Classic dynamin and DLPs form a large family of GTPases that mediate membrane fission and fusion in both eukaryotic and prokaryotic cells. Although the IniA protein in Mtb has not been functionally characterized, the crystal-structure of M. smegmatis ( Msm ) IniA showed conserved structural features with other DLPs (22) including a GTPase domain containing the four consensus elements (G1-G4) and two elongated alpha-helical bundle domains which are structurally contiguous and are also known as neck and trunk domains (Fig 3B). Msm -IniA exhibits GTPase-dependent membrane fission activity in vitro , and it localizes to the plasma membrane causing cell surface wrinkling, when overexpressed in Msm (22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations